The character: her representations and dimensions in the novel The Road to Belharith - محمد البزور, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The character is the mainstay of the narrative text and a mainstay of its mainstay, as it contributes to shaping the vision and clarifying ideas, as it is indispensable, as it is impossible to find a novel without personality, so the focus of the research revolves on this subject, trying to study the structure of the character and its representations in the novel The Road to Balharith by the novelist jamal Naji, by presenting its material, social and psychological dimensions, and accordingly the research relied on the descriptive and analytical method in exploring the character and the way it is presented in the novel.